Hasil Belajar Biologi Siswa yang Dibelajarkan dengan Menerapkan Metode Pembelajaran Improve dan Ekspositori - Firdaus Firdaus; Rasydianah Rasydianah (Universitas Muhammadiyah Enrekang, 2021)
This study was quasi-experimental research that aimed to know the biological learning achievement of students in heredity matter learned by applying IMPROVE instructional method and expository instructional method at grade IX MTsN 2 Majene. This study used a pretest-posttest non-equivalent comparison groups design. The population of this study was all of grade IX MTsN 2 Majene consist of five class. The sample of this study were students of grade IX.A MTsN 2 Majene learned by applying IMPROVE instructional method that was consisting of 22 people and students of grade IX.B MTsN 2 Majene learned by applying expository instructional method that was consisting of 22 people. The data collection techniques in this study used instruments that consist of learning achievement test in multiple-choice, completion test, and true-false form. The data analysis techniques in this study used descriptive statistics analysis and inferential statistics analysis with t-test. According to this study analysis can be concluded that (1) Biological learning achievement of students in heredity matter learned by applying IMPROVE instructional method at class IX MTsN 2 Majene had good category; (2) Biological learning achievement of students in heredity matter learned by applying expository instructional method at class IX MTsN 2 Majene had good category; (3) There was no the difference of biology learning achievement of students in heredity matter were learned by applying IMPROVE instructional method and expository instructional method at grade IX MTsN 2 Majene.